2019
DOI: 10.1097/ruq.0000000000000435
|View full text |Cite
|
Sign up to set email alerts
|

Should We Perform Transthoracic Trucut Lung Biopsies of Pleural-Based Lung Masses Under Ultrasound Guidance or Computed Tomography Guidance?

Abstract: We aimed to emphasize which method should be prioritized by comparing the ultrasound and computed tomography (CT) guidance for percutaneous transthoracic biopsy of pleural-based lung lesions in terms of comorbidity, diagnostic success, time, and costs. Approximately 700 biopsy procedures performed between 2014 and 2018 were retrospectively reviewed. The files of these patients and picture archiving and communication system were scanned. Size and localization of the lesion, pathological diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…Percutaneous biopsy under CT guidance is often used for peripheral lung lesions nearby or adjacent to the chest wall, and percutaneous biopsy for peripheral lung lesions adjacent to the chest wall can be performed under both CT and ultrasound guidance. Compared with CT-guided biopsy, ultrasound-guided biopsy for peripheral lung lesions was simple, safe, realtime visualization, fewer complications, lower cost and no radiation exposure, the diagnosis rate similar to that of CT (5)(6)(7)(8). The defect of ultrasound guidance is easy to be affected by aerated lung tissue, narrow scope of application (only suitable for peripheral lung lesions adjacent to the chest wall), in addition, mastering ultrasound-guided puncture biopsy requires a long training period, which may be the reason why CT guidance is currently preferred more than ultrasound guidance in lung lesions puncture biopsy in many countries (9,10).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Percutaneous biopsy under CT guidance is often used for peripheral lung lesions nearby or adjacent to the chest wall, and percutaneous biopsy for peripheral lung lesions adjacent to the chest wall can be performed under both CT and ultrasound guidance. Compared with CT-guided biopsy, ultrasound-guided biopsy for peripheral lung lesions was simple, safe, realtime visualization, fewer complications, lower cost and no radiation exposure, the diagnosis rate similar to that of CT (5)(6)(7)(8). The defect of ultrasound guidance is easy to be affected by aerated lung tissue, narrow scope of application (only suitable for peripheral lung lesions adjacent to the chest wall), in addition, mastering ultrasound-guided puncture biopsy requires a long training period, which may be the reason why CT guidance is currently preferred more than ultrasound guidance in lung lesions puncture biopsy in many countries (9,10).…”
Section: Introductionmentioning
confidence: 97%
“…With the wide application of high-resolution CT and the established role of low-dose helical computed tomography (CT) screening for lung cancer, pulmonary lesions are increasingly detected (1,2). Image-guided biopsy is still required for lesions that cannot be determined by CT or malignant lesions diagnosed by CT need to be clarified histopathologically or genetic types before radiotherapy or chemotherapy (3)(4)(5). Percutaneous biopsy under CT guidance is often used for peripheral lung lesions nearby or adjacent to the chest wall, and percutaneous biopsy for peripheral lung lesions adjacent to the chest wall can be performed under both CT and ultrasound guidance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, percutaneous US-guided core needle biopsy plays an increasingly important role in the management of PPLs (8). Some published studies had shown the feasibility and efficacy of US-guided percutaneous biopsy for PPLs (2,5,6,(9)(10)(11). It was reported that US-guided procedures could achieve a high success rate of 84%~96% (2), a pneumothorax rate of 1%~6%, and a hemorrhage rate of 3.3%~5.1% (2,6,12).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, US-guided percutaneous needle biopsy for PPLs was more advantageous than CT-guided procedure, such as radiation-free, convenient and cost-effective, real-time and dynamic [15][16][17]. Therefore, US-guided biopsy for PPLs that were adjacent to visceral pleura was a potentially feasible and reliable technique [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies that focused on US-guided biopsy for PPLs have veri ed the e cacy and safety of this technique [16,18,19]. However, the procedures were almost performed with 18-gauge or 20-gauge core biopsy needle.…”
Section: Introductionmentioning
confidence: 99%